The future extent of the Anthropocene epoch: A synthesis - Summerhayes, C. P.; Zalasiewicz, J.; Head, M. J.; Syvitski, J.; Barnosky, A. D.; Cearreta, A.; Fiałkiewicz-Kozieł, B.; Grinevald, J.; Leinfelder, Reinhold; McCarthy, F. M. G. (2024)
We synthesize research from complementary scientific fields to address the likely future extent and duration of the proposed Anthropocene epoch. Intensification of human-forced climate change began from about 1970 onwards with steepening increases in greenhouse gases, ocean acidification, global temperature and sea level, along with ice loss. The resulting distinction between relatively stable Holocene climatic conditions and those of the proposed Anthropocene epoch is substantial, with many aspects irreversible. The still-rising trajectory of greenhouse gas emissions is leading to yet greater and more permanent divergence of the Anthropocene from the Holocene Earth System. We focus here on the effects of the ensuing climate transformation and its impact on the likely duration of this novel state of the Earth System. Given the magnitude and rapid rise of atmospheric carbon dioxide (CO2), its long lifetime in the atmosphere, and the present disequilibrium in Earth's energy budget (expressed as the Earth's Energy Imbalance, or EEI), both temperatures and sea level must continue to rise – even with carbon emissions lowered to net zero (where anthropogenic CO2 emissions = anthropogenic CO2 removals) – until the energy budget balance is eventually restored. Even if net zero were achieved immediately, elevated global temperatures would persist for at least several tens of millennia, with expected levels of warmth by the end of this century not seen since the early Late Pliocene. Interglacial conditions are likely to persist for at least 50,000 years under already-accumulated CO2 emissions and Earth's low eccentricity orbit. Continued increases in greenhouse gas emissions are likely to extend that persistence to around 500,000 years, suppressing the pronounced expression of Milankovitch cyclicity typical of the later Pleistocene Epoch. This major perturbation alone is sufficient to justify the Anthropocene as terminating the Holocene Epoch. The wider and mostly irreversible effects of climate change, not least in ...